Benefit incidence analysis of healthcare in Bangladesh - equity matters for universal health coverage - Khan, Jahangir Am; Ahmed, Sayem; MacLennan, Mary E.; Sarker, Abdur Razzaque; Sultana, Marufa; Rahman, Hafizur E.M.R. (© 2017 Oxford University Press, 2018)
This article was published in the Health Policy and Planning [© The Author 2016.] and the definitive version is available at: http://doi.org/10.1093/heapol/czw131 The Journal's website is at: https://academic.oup.com/heapol/article/32/3/359/2907862